University's 102nd graduation ceremony, President Welty's last - Uribes, Tom::::::::: (2013)
On Saturday, May 18, more than 4,900 Fresno State students eligible for degrees will celebrate at the university's 102nd Commencement ceremony, and the last for retiring President John D. Welty.